แนวทางการบริหารงานวิชาการสำหรับโรงเรียนมัธยมศึกษาประจำจังหวัดสมุทรปราการ - ภัทรมานิต ธัชมัย; เจริญกุล นันทรัตน์ (An Online Journal of Education, 2018)
This research was a descriptive research. The purposes were to study the current and desired conditions of academic administration of provincial secondary schools in Samutprakan, and also to propose the guidelines for academic administration of provincial secondary schools in Samutprakan. The sample population used in this study were Samutprakan and Streesamutprakan Schools. Informants Included two school directors, two deputy directors in charge of academic affairs, 16 heads of subject and 80 teacher representatives from each group of subject, totally 100 respondents. This research tool was a five rating-scaled questionnaire, and semi-structured questions. Data were analyzed by frequency, percentage, mean, standard deviation, PNI modified and content analysis. The results showed that the first three priorities for each aspect of academic administration and guidelines were as follows: 1) Learning center development, in which the administrators should promote and develop resources that can improve learning quality, both inside and outside the school, 2) Promoting academic knowledge to the academic community, the administrators should encourage and support the work of exploring the needs of people in the academic community around the school for at least three communities, 3) Research conducting to improve the quality of education, the administrators should encourage teachers to use the research results to improve teaching, learning and the quality of students, at least once per academic year, 4) Developing instuction media, innovation and academic technology, the administrators should continuously conduct surveys, monitor and evaluate the use of media and technology, 5) The guideline for education, the administrators should cooperate with all teachers in school, 6) Promoting and supporting academic work for individuals, families, organizations, agencies and other institutions, the administrators should promote and support the cooperation among the people in the community to learn and share the resource together.